Determinants of antenatal care visits among adolescent pregnancy - Hernayanti, Munica Rita; Arum, Dyah Noviawati Setya; Maranata, Maranata; Laksmita, Okki Dhona (Jurnal Kesehatan Ibu dan Anak, 2024)
Adolescent pregnancy is a serious problem. Adolescent pregnancy can lead to reduced antenatal care (ANC) visits and result in significant consequences in the form of untreated pregnancy complications that will result in increased Maternal Mortality Rate (MMR). The primary objective of this study was to ascertain and scrutinize the factors influencing antenatal care (ANC) visitation patterns among adolescent pregnant women within Bantul Regency. This study is an observational analytic study with a cross-sectional design. The outcomes of the chi-square test for the facilitating factor yielded results about the level of education (p= 0.041), marriage status (p= 0.006), and pregnancy status (p= 0.000) while on the reinforcing factor of family support (p= 0.027). The results of this study's logistic regression test stated that health worker support (p= 0.020) and pregnancy status (p= 0.001). The conclusion of this research suggests that the pivotal determinants significantly influencing ANC utilization among adolescent pregnant women in Bantul Regency are the presence of health worker support and the particular status of pregnancy.